2018
DOI: 10.1021/acsami.8b07485
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Patterning by Electron Beam-Assisted Carbon Lithography

Abstract: We report on the proof of principle of a scalable method for writing the magnetic state by electron-stimulated molecular dissociative adsorption on ultrathin Co on Re(0001). Intense microfocused low-energy electron beams are used to promote the formation of surface carbides and graphitic carbon through the fragmentation of carbon monoxide. Upon annealing at the CO desorption temperature, carbon persists in the irradiated areas, whereas the clean surface is recovered elsewhere, giving origin to chemical pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 60 publications
3
19
0
Order By: Relevance
“…Fig. 8(a) shows the XMCD-PEEM images acquired at zero field at different temperatures between 25 and 375 C. The images show a pattern with alternating dark and bright regions, which, in agreement with our previous work, is interpreted as being due to out-of-plane domains with an antiparallel orientation of the magnetization (Genoni et al, 2018). The XMCD asymmetry is close to 6%, as expected for metallic Co in our measurement geometry (grazing incidence illumination at 16 reduces the contrast by a factor of about 3.5 for the out-of-plane magnetization compared to the in-plane magnetization).…”
Section: Magnetism In Graphene/co/re(0001)supporting
confidence: 87%
See 3 more Smart Citations
“…Fig. 8(a) shows the XMCD-PEEM images acquired at zero field at different temperatures between 25 and 375 C. The images show a pattern with alternating dark and bright regions, which, in agreement with our previous work, is interpreted as being due to out-of-plane domains with an antiparallel orientation of the magnetization (Genoni et al, 2018). The XMCD asymmetry is close to 6%, as expected for metallic Co in our measurement geometry (grazing incidence illumination at 16 reduces the contrast by a factor of about 3.5 for the out-of-plane magnetization compared to the in-plane magnetization).…”
Section: Magnetism In Graphene/co/re(0001)supporting
confidence: 87%
“…With this motivation, we recently investigated the magnetic properties of ultra-thin Co on Re(0001), focusing our attention on the effect of carbon adsorption on the film magnetic anisotropy. Our previous work had established a means to graft the magnetic state by accumulating carbon adspecies on the cobalt surface using e-beam-stimulated CO fragmentation (Genuzio et al, 2019a;Genoni et al, 2018). Interestingly, we found that these species can be converted to a graphitic overlayer upon performing a moderate thermal treatment, without compromising the integrity of the ultra-thin Co film.…”
Section: Magnetism In Graphene/co/re(0001)mentioning
confidence: 88%
See 2 more Smart Citations
“…The XMCD-PEEM images comparing the magnetic state of Co before and after air exposure are shown in parts a and b of Figure . The labels provide information on the magnetic anisotropy, which was determined in accord to our previous study on this system . Initially, the nonirradiated regions exhibit in-plane magnetization, as can be deduced from the large contrast that is observed outside the disk.…”
Section: Applicationsmentioning
confidence: 83%